Operative Techniques for Cervical Radiculopathy and Myelopathy - R. G. Kavanagh; J. S. Butler; J. M. O'Byrne; A. R. Poynton (Advances in Orthopedics)
Cervical spondylosis is a common problem encountered in modern orthopaedic practice. It is associated with significant patient morbidity related to the consequent radiculopathic and myelopathic symptoms. Operative intervention for this condition is generally indicated if conservative measures fail; however there are some circumstances in which urgent surgical intervention is necessary. Planning any surgical intervention must take into account a number of variables including, but not limited to, the nature, location and extent of the pathology, a history of previous operative interventions, and patient co-morbidities. There are many different surgical options and a multitude of different procedures have been described using both the anterior and posterior approaches to the cervical spine. The use of autograft to achieve cervical fusion is still the gold standard with allograft showing similar results; however fusion techniques are constantly evolving with novel synthetic bone graft substitutes now widely available.